IOL-Induced Extreme Blur to Alleviate Intractable Diplopia Secondary to Dragged-Fovea Diplopia Syndrome. Issue 2 (3rd April 2019) - Ismaiel, Noor; Olson, Joshua; Zabrowski, Cheryl; Lee, Michael S.; McClelland, Collin M.
ABSTRACT: A 73-year-old male presented with one year of intractable binocular diplopia and metamorphopsia in the right eye. He was unable to maintain fusion with prismatic correction, refused cosmetically noticeable forms of occlusion, and was not an occlusive contact lens candidate due to chronic neuropathy affecting his hands. The patient underwent cataract surgery with placement of a high plus intraocular lens to induce extreme blur. The uncomplicated procedure was successful in eliminating his diplopia. Cataract extraction with a high minus refractive target is an option for treating intractable diplopia associated with dragged-fovea diplopia syndrome.